Semantik Leksikal Pantun dalam Sastra Sasak - Lalu Purnama Zulkarnain (Jurnal Ilmiah Telaah, 2023)
Lexical semantics of pantu in Sasak literature Semantic studies. This study aims to analyze pantun texts in Sasak literature. By using semantic theory which discusses lexical semantics The problem studied in this study is the use of Sasak rhymes, lexical semantics contained in pantun texts in Sasak literature, namely rhymes for advice, rhymes for youth, and rhymes for religion. This research is a research with a qualitative approach that is descriptive. The analysis aims to collect and describe the lexical semantics found in pantun texts in Sasak literature. The final finding in this study is that there is lexical semantics in each stanza of the pantun. From the lexical semantics, there are several messages in the pantun that are meaningful to listeners or the public.